2008
DOI: 10.1111/j.1439-0426.2008.01093.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the oocyte envelopes of some Eurasian acipenserids

Abstract: The cellular and acellular envelopes of oocytes and follicles at the ultrastructural level are described for some acipenserids. The objective was to identify whether morphological features exist that can assist in discrimination of caviar products in trade originating from various species. The follicular envelopes include one thecal and one follicular cell layer separated by a basal lamina. The oocyte is surrounded by four acellular layers: (i) the internal zona radiata directly in contact with the oocyte plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 15 publications
4
44
0
Order By: Relevance
“…(e) , Vacuoles containing material for the vitelline envelope in the peripheral ooplasm; er, endoplasmic reticulum; m, mitochondria; ld, lipid droplets. (f) Vitelline envelope: FL, the filamentous layer; t, trabecules; t1 (zre), trabecular layer t1 = zona radiata externa (Debus et al , 2008); , fibrils; ch, alveolar chorion; , the canals; O, oocyte; mv, oocyte microvilli.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(e) , Vacuoles containing material for the vitelline envelope in the peripheral ooplasm; er, endoplasmic reticulum; m, mitochondria; ld, lipid droplets. (f) Vitelline envelope: FL, the filamentous layer; t, trabecules; t1 (zre), trabecular layer t1 = zona radiata externa (Debus et al , 2008); , fibrils; ch, alveolar chorion; , the canals; O, oocyte; mv, oocyte microvilli.…”
Section: Resultsmentioning
confidence: 99%
“…During their formation in ovarian follicles, the egg envelopes develop numerous canals. Due to this process, either all the envelopes or only the vitelline envelope are referred to as zona radiata (Le Menn & Pelissero, 1991; Riehl, 1999; Debus et al , 2008). The main functions of egg envelopes include the fixation of a deposited egg to the substratum, sperm attraction, prevention of polyspermy and antibacterial and mechanical protection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eggs of sturgeons including the investigated species, Acipenser gueldenstaedtii and Acipenser baerii, are equipped with multiple micropyles lo-cated at the animal region that allow entry of numerous spermatozoa (CHERR & CLARK 1982;DEBUS et al 2008;PSENICKA et al 2010;¯ELAZOWSKA 2010). Observation of egg surfaces in A. transmontanus and in A. baerii during gamete fusion revealed that after incorporation of a spermatozoon, the contents of cortical granules was released into the space between the oocyte and egg envelope.…”
mentioning
confidence: 99%
“…In oocytes of the investigated species, the layer of egg envelope located most externally to the oolemma slightly thickens. In A. baerii this layer is called the adhesive layer or jelly coat (DEBUS et al 2008;PSENICKA et al 2010). In A. gueldenstaedtii this layer is referred to as the extrachorion (¯ELAZOWSKA 2010).…”
mentioning
confidence: 99%